Respuestas

¡La mejor respuesta!
2013-10-20T21:02:29+02:00


4(x - 3) - 3(y - 4) = 0
       4x - 12 - 3y + 12 = 0
             4x - 3y = 0              (1)

5(x - 4) + 2(y + 2) = 0
5x - 20 + 2y + 4 = 0
             5x + 2y - 16 = 0
             5x + 2y = 16             (2)

(1) x (2)         8x - 6y = 0       (1.1)
(2) x (3)       15x + 6y = 48     (2.1)
(1.1) + 2.1)   23x = 48
                                       x = 48/23
En (1)
             4(48/23) - 3y = 0
                      3y = 192/23
                        y = 192/(3x23)
                        y = 64/23
Solución del sistema:
    x = 48/23
    y = 64/23
Ninguna de las alternativas